Digital Currencies and Cryptocurrency Market Treath - Minaudo, Massimiliano (International Journal For Research In Educational Studies, 2019)
After the prevalence of digital currency and mainly of Bitcoin the financial world has certainly changed, initially, it seemed that some currencies had surpassed their "mother" (Bitcoin precisely) now some new uncertainties surface and the task of the present research is to remove the veil of mystery that envelops the new coins and bring to light concrete facts and exact documentation. Is it still worth investing? What to do in the current landscape and what exactly has happened will be explained here and then analyzed to better understand the metamorphosis that took place.